STRATEGI PEMERINTAH INDONESIA UNTUK PENCAPAIAN TARGET KE-6 MDGs MELALUI BANTUAN THE GLOBAL FUND TAHUN 2003 - 2013 - Astiti Tajem, Putu Ika; Fasisaka, Idin; Intan Parameswari, Anak Agung Ayu (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2015)
A BS TRAK Nowadays, the Indonesian Government strategy in achieving the 6th MDG targets through grant aid from foreign parties , namely The Global Fund. The high rates of spread of infectious diseases in Indonesia such as HIV and AIDS, Tuberculosis, and Malaria have been a problem that attracted the attention of world community. Therefore, in 2000 the Government of Indonesia and 189 UN member states gathered together created an agreement that is known as the Millennium Declaration of the Millennium Development Goals (MDGs). The 6th target of MDGs is to fight HIV & AIDS, malaria, and other transmitted diseases. The Global Fund as an international organization with the vision and mission of combating the spread of infectious diseases through a project, named Global Fund to Fight AIDS, Tuberculosis, and Malaria (GFATM). Indonesia is one of the countries that have been involved in the project. The Global Fund to provide assistance in the form of grant aid to the Government of Indonesia to combat the spread of transmitted diseases. In this study shows Indonesian Government strategy in achieving the 6th target of MDG can be implemented by carrying out monitoring and evaluation of programs, as well as conduct training through grant aid from the Global Fund. This research used  qualitative approach and examined using the concept of Principal and Agent, Foreign Assistance and the National Health Development Strategy in 2003-2013 . Keywords : Indonesian Government strategy, assistance  fund, The Global Fund, The 6 th target of  MDGs